1970
DOI: 10.3329/bjms.v10i2.7803
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis-B surface antigen (HBsAg) positivity in Solapur District, Maharashtra State, India

Abstract: Background: Hepatitis B virus is a partially double-stranded circular DNA virus and is a member of the Hepadnaviridae family. The virus consists of a core capsid which contains viral DNA and this is surrounded by an envelope containing surface antigen (HBsAg). Both whole, incomplete virus particles, consisting entirely of HBsAg, are produced during replication of HBV. The HBsAg particles vary greatly in morphology and are found in high concentrations in early acute infection and continue to be produced in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The widely quoted figure of a carrier rate in India is 4.7% Similar other studies conducted show variable results in Out of total patients 756/1463(51.67%) were males and 707/1463(48.23%) were females. Seropositivity was seen more observed HBsAg positivity [17] also reported positivity of HbsAg was more prevalent [10] also observed higher [18] explained low seropositivity among females because probably they clear HBV more efficiently in comparison to males. Our study shows comparable findings of hepatitis B 45 years was found to have highest prevalence rate with seropositivity of 15/279(5.38%).…”
Section: : Seroprevalence Of Hbsag As Documented By Different Authorsmentioning
confidence: 87%
“…The widely quoted figure of a carrier rate in India is 4.7% Similar other studies conducted show variable results in Out of total patients 756/1463(51.67%) were males and 707/1463(48.23%) were females. Seropositivity was seen more observed HBsAg positivity [17] also reported positivity of HbsAg was more prevalent [10] also observed higher [18] explained low seropositivity among females because probably they clear HBV more efficiently in comparison to males. Our study shows comparable findings of hepatitis B 45 years was found to have highest prevalence rate with seropositivity of 15/279(5.38%).…”
Section: : Seroprevalence Of Hbsag As Documented By Different Authorsmentioning
confidence: 87%